Pragmatic Criticism of Lingkar Tanah Lingkar Air Novel by Ahmad Tohari - Ikin Syamsudin Adeani; R.Bunga Febriani (Universitas Bengkulu, 2020)
The research backgrounds are conventional literary learning, less supportive learning facilities, the low students’ reading interest on the literary books, especially on the books of literary criticism, and the lack of grade writing ability of literary criticism. This research is aimed to recognize the benefits of pragmatic criticism on the novel Lingkar Tanah Lingkar Air (LTLA) written by Ahmad Tohari. The method used in this research is descriptive method. The results of this research are as follows: (1) LTLA novel tells about Amid, Kiram, Jun, Jalal, and Kang Suyud as Hezbollah forces whose basic struggle is lillahi taala (because of Allah), (2) LTLA novel is interpreted as a novel about the conflict of inner-soul in keeping their faith as moslem and their hate to Republican Army as many of them did not pray, and (3) as an evaluation of LTLA, background of this story based on the life of Indonesian people since the days of the Darul Islam ruled by Kartosuwiryo. The conclusions of LTLA novel are educative, namely: (1) inviting to keep loyal to the Indonesian state and its people; (2) carrying out the commands of religion (Islam) properly and correctly; and (3) love each other’s soul and inner fellow people.